2019
DOI: 10.1377/hlthaff.2018.05386
|View full text |Cite
|
Sign up to set email alerts
|

ACO Contracts With Downside Financial Risk Growing, But Still In The Minority

Abstract: Success of the accountable care organization model may require stronger financial incentives, potentially by including downside financial risk in contracts. Using the National Survey of ACOs, we explored changes in ACO structure and contracts over time. Though the number of ACO contracts and proportion with multiple contracts has grown, the proportion of ACOs bearing downside risk increased only modestly.Accountable care organizations (ACOs) have emerged as one of the most broadly implemented value-based payme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 5 publications
0
10
0
1
Order By: Relevance
“…Zur Kostenreduzierung fokussieren ACOs auf die Optimierung von Patientenpfaden 53 , die Versorgungskoordination 54 und die Reduzierung von Leistungen von niedriger medizinischer Wertigkeit 55 . Auch versuchen sie, die Leistungsinanspruchnahme außerhalb des ACO-Netzwerks zu reduzieren 56 57 .…”
Section: Ergebnisseunclassified
“…Zur Kostenreduzierung fokussieren ACOs auf die Optimierung von Patientenpfaden 53 , die Versorgungskoordination 54 und die Reduzierung von Leistungen von niedriger medizinischer Wertigkeit 55 . Auch versuchen sie, die Leistungsinanspruchnahme außerhalb des ACO-Netzwerks zu reduzieren 56 57 .…”
Section: Ergebnisseunclassified
“…3,33 Most ACOs had to rely on patients to tell them about upcoming or recent specialist appointments. Only two ACOs, both part of highly centralized healthcare delivery systems, which are only half of ACOs in 2018, 42 implemented system-wide initiatives to fully integrate specialist and primary care clinicians into care plans. Even ACOs which include hospitals in their contract may struggle to coordinate care across settings, and they report similar care delivery capabilities as ACOs without a hospital.…”
Section: Discussionmentioning
confidence: 99%
“…A study based on the National Survey of ACOs found that, between 2012 and 2018, the proportion of Medicare ACOs with 2-sided risk was smaller than those of commercial ACOs and multicontract ACOs. 12 A 2018 survey conducted by the National Association of ACOs revealed that, among Track 1 SSP ACOs facing the policy requirement to move to 2-sided risk in their next contract, 71% of respondents indicated that they were likely to leave the program if being forced to assume downside risk. 13 ACOs with different characteristics may be more or less prepared to assume downside risk.…”
Section: Introductionmentioning
confidence: 99%